Average Intensity and Wavelength of the Emitted Radiations from Earth Surface with Error Analysis - Neupane, Rajendra; Gauli, Hari Ram Krishna; Rai, Krishna Bahadur (Nepal Journal of Science and Technology, 2022)
This research finds the spectrum and the net intensity of the emitted radiations from the earth surface at different temperatures of 273, 283, 293, 303, 313, and 323 K. The intensity of the radiations emitted from the surface varies by 272.013 Wm-2 between 273 K and 323 K surface temperatures at emissivity 0.9. The average intensity for emissivity 0.9 is 410.405 Wm-2, with a standard deviation of 101.94 Wm-2 and standard error 41.616. The calculated mean emitted flux is found 8.9482 W/m2/sr/µm for 0.9 emissivity. At emissivity of 0.96, the desert emits radiation with an average intensity of 437.77 Wm-2 having standard deviation 108.708 Wm-2 and standard error 44.379. These large values of standard deviation and standard error are due to the large difference between any two adjacent values of intensity of the emitted radiations. Standard error comparisons between the emissivity calculations of 0.9 and 0.96 show that the intensity in emissivity 0.9 is more appropriate than the intensity in emissivity 0.96 in determining the average value of intensity of emitted radiations. The difference between the calculated and standard values for the average intensity of radiation radiated from the earth’s surface is about 17%.